TESTS OF ARRANGEMENTS IN A PROTOTYPE OF A STEAM GENERATOR IN AN ABSORPTION REFRIGERATION SYSTEM - Santos, R. F. M.; Cezar, K. L.; Rocha, P. A. C.; Lima, R. J. P.; Silva, M. E. V. da; Alcantara, S. C. S. (Revista de Engenharia Térmica, 2019)
This paper presents a proposal to optimize the prototype II of a steam generator, developed by the Cooperativa de Pesquisa Norte/Nordeste de Gas Natural, RECOGÁS - UFPB, which is a component of an absorption refrigeration system of water and lithium bromide triggered by direct burning of natural gas. The optimization was carried out through changes in the arrangement, geometry, and number of the heat exchanger pipes. It was developed a computational code using F-Chart software Engineering Equation Solver® (EES), applying the principles of heat transfer to all the different geometries. As a result, their respective coefficients of heat transfer, heat flow rate and other parameters of the process were obtained. The findings are organized in a table and represented in graphs generated by the EES software, allowing to verify which factors had a greater influence on the process, as well as the most efficient geometries. Internal convection was identified as the governing factor in the heat transfer process. Some of the geometries presented satisfactory values to the product of overall heat transfer coefficient and surface area (UA) and also to the heat transfer rate in the steam generator. Other ones presented a better thermal efficiency relation with the amount of volume occupied in the steam generator. Some geometries did not present satisfactory values under any aspect.